Q-Analogue of Holder’s and Minkowski’s Integral Inequalities on Finite Intervals and Generalization - Bhatta, Suresh; Bhatta, Chet Raj (Journal of Advanced College of Engineering and Management, 2021)
In recent years, the topic on Holder’s and Minkowski’s inequalities has been studied by several researchers and variety of new results has been developed on their variants, extensions and generalizations. In this paper we give the extension to the generalized q- Holder’s integral inequality and by using it we also establish the generalization on q- Minkowski’s integral inequality on the finite interval [a, b]